Direct introduction of elemental sulfur into polystyrene: A new method of preparing polymeric materials with both high refractive index and Abbe number. (10th October 2019) - Jiang, Liping; Kong, Ruixia; Yi, Yuliang; Yang, Siqi; Mei, Yu; Feng, Xiaofei; Yao, Zhanhai; Zhang, Jianfu
Abstract: The present work proposes a facile but effective method for the design and synthesis of optical polymers with both high refractive index (RI) and Abbe number (AN) by the direct introduction and dispersal of elemental sulfur in polystyrene (PS). The excellent dispersal of the reaction products of elemental sulfur with styrene (St-S) in the PS result in the highest RI of 1.6220 and AN of 27.3. The acceptable uniform dispersal of elemental sulfur in the PS is verified by photographic analysis, optical transmission spectra, scanning electron microscopy, and energy dispersive spectroscopy analyses. The thermal properties of polymeric materials were investigated using thermogravimetric analysis and differential scanning calorimeter. The proposed strategy not only provides a new high RI material for optical applications, but also offers new opportunities for the dispersal of substances into polymeric materials. Graphical abstract: Image 1 Highlights: High RI polymers are prepared by direct introduction of elemental sulfur in PS. Sulfur-containing polymers exhibit the highest RI of 1.6220 and Abbe number of 27.3. The uniform dispersal of elemental sulfur into PS is well identified.